DEVELOPM ENT OF SMALL BUSINESS AND PRIVATE ENTERPRISES IN NAMANGAN, REPUBLIC OF UZBEKISTAN - Soliev, Ibodulla Ismatullaevich; Ahmedov, Rahmonjon Mamadjonovich; Tursunalievich, Abdulhakimov Zuhrali (The journal of contemporary issues in business and government, 2021)
This article develops ways to accelerate the development of small business and private entrepreneurship in the Republic of Uzbekistan, prepares scientific developments and practical recommendations for future development of the industry.